2009
DOI: 10.1095/biolreprod.108.070250
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Membrane Estrogen Receptor in Zebrafish with Homology to Mammalian GPER and Its High Expression in Early Germ Cells of the Testis1

Abstract: To study the rapid action of estrogen on the male reproductive system in teleost, a full-length cDNA homologous to the seven-transmembrane receptor GPER of humans and rodents was cloned from the testis of zebrafish. Biological characterization of this cloned zebrafish gper was performed based on its functional expression in cultured eukaryotic cells. Saturation analysis and Scatchard plotting of [(3)H]-estradiol binding to plasma membranes of gper-transfected COS-7 cells and cAMP response element transactivati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
66
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(73 citation statements)
references
References 42 publications
4
66
0
3
Order By: Relevance
“…7 mM) was shown to be rapid (within 5 min) and was transduced by a membrane-associated ER (Loomis & Thomas 2000). Recently, a membrane associated ER, homologous to mammalian GPER, has been cloned from zebrafish, and is expressed in testis (Liu et al 2009). The E 2 concentration used in the current study (10 nM) could have been sufficient to activate the zebrafish Gper.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…7 mM) was shown to be rapid (within 5 min) and was transduced by a membrane-associated ER (Loomis & Thomas 2000). Recently, a membrane associated ER, homologous to mammalian GPER, has been cloned from zebrafish, and is expressed in testis (Liu et al 2009). The E 2 concentration used in the current study (10 nM) could have been sufficient to activate the zebrafish Gper.…”
Section: Discussionmentioning
confidence: 82%
“…However, the direct effects of oestrogen in the zebrafish testis were comparatively weak and possibly mediated via a nuclear Er, considering the prolonged time required for them to become evident, while the binding of E 2 to zebrafish Gper, although of high affinity (K d Z2 . 8 nM), was characterized by both rapid association and dissociation (Liu et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…We observed that, in the tissues analyzed of gilthead seabream, the higher expression of GPER expression was observed in liver and gonad. In fish, GPER has been detected in Atlantic croaker and zebrafish gonads, and its activity has been related with the maturation of oocytes (51)(52)(53). Considerably, GPER is expressed in spleen and HK, the main hematopoietic organ in fish.…”
Section: Discussionmentioning
confidence: 99%
“…Centrifugation methods have been employed for the preparation of subcellular fractions containing GPER that exhibit specific binding with filtration assays typically used to separate free from bound ligand in membrane fractions. This approach was first demonstrated in ER-negative cell lines using the human wild-type and recombinant receptor in SKBR3 and HEK293 cells, respectively , and later in human urothelial cell membranes (Teng et al, 2008) and with the zebrafish ortholog (Liu et al, 2009b). The lability of GPER requires short incubation times, low temperature (4°C), and the inclusion of protease inhibitors for reproducible ligand binding assays (Filardo and Thomas, 2012).…”
Section: A Receptor Binding Characteristics and Assays For G Proteinmentioning
confidence: 99%
“…The lability of GPER requires short incubation times, low temperature (4°C), and the inclusion of protease inhibitors for reproducible ligand binding assays (Filardo and Thomas, 2012). Measured K d values for 17b-estradiol binding to GPER in membrane preparations from divergent species including zebrafish (Liu et al, 2009b), croaker (Pang et al, 2008), and recombinant human are very similar (2.3-3.3 nM) (Filardo and Thomas, 2012). The description of [ 3 H]E2 binding to GPER in membrane preparations as "limited capacity" Pang et al, 2008) likely reflects the low abundance or instability of the receptor in such preparations but has no functional implications.…”
Section: A Receptor Binding Characteristics and Assays For G Proteinmentioning
confidence: 99%